PERBEDAAN KOMITMEN IBU DALAM PEMBERIAN IMUNISASI DPT 2 PADA BAYI USIA DIBAWAH 3 BULAN SEBELUM DAN SESUDAH PEMBERIAN HEALTH PROMOTION MODEL NOLA J., PANDER - Agus Priyanto (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Parent's commitment to immunizing hertoddler is one of the obstacles to achieving thesuccess of the immunization coverage target.Immunization itself is very important as an effort toprevent disease in children and has beenrecommended to the community. Based onpreliminary study results, researchers conductedinterviews with local midwives obtained data thereare some children who have not immunized DPT 2 itis strengthened by interviews with 10 mothers whodo not immunize DPT 2 on the baby for fear of sideeffects. The aim of this research is to know thedifference of mother's commitment before and aftergiving Health Promotion Model Nola J.Pander. This research used one group design pre post testdesign. With two variables, independent variablesare health education, dependent variable of mother'scommitment. The data collection used questionaire,data taken from respondent such as mother withpopulation of 44 responden with amount the sampelcounted 30 mother were taken with simple randomsampling technique, at Burneh community healthcenter. The results were analyzed descriptively andcorrelated using the Wilcoxon Match Pairs Test The results were analyzed descriptively andcorrelated using the Wilcoxon Match Pairs Test test.Analysis of Wilcoxon Match Pairs Test with p value =0.000 so H1 accepted means there are differencesbefore and after health education with Nola J.Panderapproach. There are still several other factors that influence thecommitment, among others, family and culturalfactors that are not examined in this study, so thatthe next researcher is expected to do research onthe influence of these factors on the mother'scommitment